Orthopaedic Simulation of a Morton’s Extension to Test the Effect on Plantar Pressures of Each Metatarsal Head in Patients without Deformity: A Pre-Post-Test Study - Anna Sánchez-Serena; Marta Elena Losa-Iglesias; Ricardo Becerro-de-Bengoa-Vallejo; Ángel Morales-Ponce; Alfredo Soriano-Medrano; Eduardo Pérez-Boal; Jessica Grande-del-Arco; Israel Casado-Hernández; Eva María Martínez-Jiménez (Diagnostics, 2023)
Background: the area beneath the metatarsal heads is a common location of foot pain, which is often associated with high plantar pressures. The aim of this study was to determine the effect of the application of a Morton’s extension on the pressure in the metatarsal bones of the foot using a pressure platform. Methods: twenty-five subjects without musculoskeletal pathology were selected for this study, and an experiment was conducted with them as the subjects, before and after application of a Morton’s extension. The foot regions were divided into the forefoot (transversely subdivided into six areas corresponding to the first, second, third, fourth, and fifth metatarsal heads, and the hallux), midfoot, and rearfoot, and then the maximum and average pressures exerted at each region were measured before and after placing a Morton’s extension. Main findings: we found a pressure reduction, with a p-value less than (p < 0.05), in the head of the second and third metatarsals in statics and dynamics. Conclusions: we can conclude that the Morton’s extension produces a variation in plantar pressures on the lesser metatarsals. The application of a Morton’s extension may be beneficial for the management of forefoot pathology. This study will help clinicians consider various tools to treat forefoot disorders. NCT05879094 (ClinicalTrial.gov (accessed on 18 May 2023)).